Impact assessment of cold-adapted Pseudomonas jesenii MP1 and Pseudomonas palleroniana N26 on Phaseolus vulgaris yield and soil health - Suyal, Deep Chandra; Khan, Amir; Singh, Ajay Veer; Agarwal, Aparna; Pareek, Navneet; Sah, Vinod Kumar; Goel, Reeta (Frontiers in Agronomy, 2023)
The poor agriculture practices, fragmented land holdings, fluctuating climatic conditions, and minimal external inputs lead to nutrient deficiency in the Himalayan agroecosystems. Because of the risks associated with chemical fertilizers their implication is a big question mark. Therefore, two previously characterized plant growth-promoting rhizobacteria Pseudomonas jesenii MP1 and Pseudomonas palleroniana N26 were employed to enhance kidney bean productivity and soil health at farmer’s field of Harsil and Chakrata regions of Uttarakhand Himalayas. The field trial studies have revealed that MP1 and N26 treatment resulted in 25.62 % and 37.23 % higher grain yield than respective uninoculated controls at Harsil and Chakrata regions, respectively. Further, the bacterial treatments have significantly increased nitrogen, phosphorus, and potassium levels in the soils. The comparative metagenome analysis revealed the dominance of Proteobacteria at Harsil regions while Actinobacteria at Chakrata. Further, the MP1 treatment had increased Firmicutes percentage over uninoculated control at both locations. Conclusively, the application of cold adaptive Pseudomonas jesenii MP1 and Pseudomonas palleroniana N26 improved the grain yield and soil health status of the Himalayan agroecosystems. Therefore, they can be explored as an eco-friendly alternative for the commercial production of kidney beans.